The Effect Stock Split on Abnormal Return and Stock Trading Volume - Andi Agung Adiguna; Syamsu Alam; Fauzi R Rahim (Magister Management, Hasanuddin University, 2022)
The purpose of this study is to examine and analyze the effect of stock split on abnormal return and stock trading volume in manufacturing sector companies listed on the Indonesia Stock Exchange. This type of research uses quantitative descriptive analysis. The population in this study was 40 companies registered in Manufacturing. Sampling in this study used the purposive sampling method in which the sample was taken with certain criteria to have a representative sample. Based on the results of statistical tests, it was found that the announcement of a stock split has no significant effect on abnormal returns so a positive abnormal return indicates that the stock split provides good news for investors, but a negative abnormal return indicates a stock split is a bad news so that it will affect on investor confidence to invest. While the results of the subsequent statistical tests showed that there is a significant difference between the average trading volume activity before and after the stock split announcement.